2015
DOI: 10.1155/2015/908708
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Overall and Progression-Free Survival of Nigerian Patients with Philadelphia-Positive Chronic Myeloid Leukemia

Abstract: Objective. The tyrosine kinase inhibitors have markedly changed the disease course for patients with Ph+ and/or BCR-ABL1 + chronic myeloid leukemia (CML). This study was embarked upon to assess the long-term effects of imatinib therapy on survival in adult Nigerian patients with CML. Methods. All adult patients on imatinib (400–600 mg) seen from July 2003 to December 2010 were assessed. Male/female distribution was 171/101, with a median age of 38 (range, 20–75) years. Overall survival (OS) and progression-fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
6
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 20 publications
7
6
2
Order By: Relevance
“…This has consistently been established in previous studies and in all reports from our cohort, including this study. 15,19 In contrast to what has been reported from other CML studies including our earlier reports, this study has established that anemia at diagnosis is an independent prognostic factor predicting the poor OS. Indeed, the recent study by Saußele et al, 20 in which 1519 German CML patients were retrospectively studied for the impact of comorbidities on survival outcomes, found that OS was affected more by comorbidities than by CML and that hemoglobin level had no significant influence.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…This has consistently been established in previous studies and in all reports from our cohort, including this study. 15,19 In contrast to what has been reported from other CML studies including our earlier reports, this study has established that anemia at diagnosis is an independent prognostic factor predicting the poor OS. Indeed, the recent study by Saußele et al, 20 in which 1519 German CML patients were retrospectively studied for the impact of comorbidities on survival outcomes, found that OS was affected more by comorbidities than by CML and that hemoglobin level had no significant influence.…”
Section: Discussioncontrasting
confidence: 99%
“…The median age of 37 years is similar to what we had reported in our earlier studies comprising fewer of these patients, 36 years in 2008 ( n = 98) and 38 years in 2015 ( n = 272), 14,15 and what has been reported from Ivory Coast but differs significantly from populations in the Western world. 17,18 Similar to incidence, it is equally unclear whether these are mere reflections of the younger population distribution as found in most developing countries or a true difference in CML biology.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Mechanisms of resistance to TKIs in CML include genomic amplifications, point mutations of the ABL tyrosine kinase domain, and emergence of ACAs [15]. The median age of patients at diagnosis was 37 years which is comparable to previous studies in Pakistan, Nigeria, Mexico [16], [17], [18], and previous Egyptian reports [19], [20]. In our study, we found that patients <40 years tended to develop ACAs more than patients ≥40 years (55% vs. 30%), respectively (p = 0.034).…”
Section: Discussionsupporting
confidence: 75%